Introduction to the Special Thematic Issue "Virtual Reality and Eye Tracking" - Béatrice Hasler; Rudolf Groner (Bern Open Publishing, 2024)
Technological advancements have made it possible to integrate eye tracking in virtual reality (VR) and augmented reality (AR). Many new VR/AR headsets already include eye tracking as a standard feature. While its application previously has been mostly limited to research, we now see installations of eye tracking into consumer level VR products in entertainment, training, and therapy.  The combination of eye tracking and VR creates new opportunities for end users, creators, and researchers alike: The high level of immersion - while shielded from visual distractions of the physical environment - leads to natural behavior inside the virtual environment. This enables researchers to study how humans perceive and interact with three-dimensional environments in experimentally controlled, ecologically valid settings. Simultaneously, eye tracking in VR poses new challenges to gaze analyses and requires the establishment of new tools and best practices in gaze interaction and psychological research from controlling influence factors, such as simulator sickness, to adaptations of algorithms in various situations. This thematic special issue introduces and discusses novel applications, challenges and possibilities of eye tracking and gaze interaction in VR from an interdisciplinary perspective, including contributions from the fields of psychology, human-computer interaction, human factors, engineering, neuroscience, and education. It addresses a variety of issues and topics, such as practical guidelines for VR-based eye tracking technologies, exploring new research avenues, evaluation of gaze-based assessments, and training interventions.